2020
DOI: 10.1002/cctc.202001482
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Pt−Fe and Pt−Ni3 Surface Catalytic Mechanisms towards Contrasting Products in Chemoselective Hydrogenation of α,β‐Unsaturated Aldehydes

Abstract: Noble‐metal catalysts serve as an irreplaceable role in pharmaceutical, perfume and fine chemicals fields. However, there still remains a grand challenge in controlling chemoselectivity. Herein, we have synthesized a bimetallic nanostructure supported on porous metal‐organic frameworks (Pt−Fe/UiO‐66, Pt‐Ni3/UiO‐66), in which Pt nanoparticles was modified with non‐noble metal (Fe or Ni) directly. The as‐synthesized catalysts can function as a switch for selective hydrogenation of α,β‐unsaturated aldehydes to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…Since our dilute alloy catalysts show no bulk NiPt phase and minimal evidence of charge transfer between Ni and Pt, this absence of selective C=O bond hydrogenation is in agreement with the previously reported results. It has also been reported that a Pt‐Ni 3 /UiO‐66 catalyst was primarily selective to the partially saturated aldehyde [10] . These results also support the hypothesis described above that the nanoparticle surface is predominantly Ni, as substantial Pt on the surface would be expected to change the selectivity as compared to Ni/SiO 2 .…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Since our dilute alloy catalysts show no bulk NiPt phase and minimal evidence of charge transfer between Ni and Pt, this absence of selective C=O bond hydrogenation is in agreement with the previously reported results. It has also been reported that a Pt‐Ni 3 /UiO‐66 catalyst was primarily selective to the partially saturated aldehyde [10] . These results also support the hypothesis described above that the nanoparticle surface is predominantly Ni, as substantial Pt on the surface would be expected to change the selectivity as compared to Ni/SiO 2 .…”
Section: Resultssupporting
confidence: 85%
“…It has also been reported that a Pt-Ni 3 /UiO-66 catalyst was primarily selective to the partially saturated aldehyde. [10] These results also support the hypothesis described above that the nanoparticle surface is predominantly Ni, as substantial Pt on the surface would be expected to change the selectivity as compared to Ni/SiO 2 . This is not expected to be the only adsorption mode for citral, however, as the unsaturated alcohol selectivity observed over Cu suggests some preferential C=O bond hydrogenation.…”
Section: Chemcatchemsupporting
confidence: 87%
See 2 more Smart Citations
“…The catalysts have gradually evolved from monometallic to multimetallic structures. Particularly, the multimetallic catalysts containing precious metals can significantly reduce the amount of the noble metals and simultaneously improve their catalytic performance (activity, selectivity and stability), due to synergetic effect among related species, [1–19] For instance, a small amount of Rh was added to a Pt‐based catalyst, forming a Pt−Rh bimetallic system, its stability for the catalytic oxidation of ammonia was markedly improved [20] . The Au/SiO 2 , Au/ZrO 2 , Au/TiO 2 , Au/ZnO monometallic and Au−In/ZnO bimetallic supported catalysts were prepared by Claus et al ., [21,22] and these catalysts were applied in selective hydrogenation of acrolein.…”
Section: Introductionmentioning
confidence: 99%